Distribution of Eucoilinae (Hymenoptera, Cynipoidea, Figitidae) - Gallardo, Fabiana Edith (2017)
Euxestophaga Gallardo, a new genus of Eucoilinae (Hymenoptera, Cynipoidea, Figitidae) and Euxestophaga argentinensis Gallardo, sp. n. from Argentina, are described and illustrated.